Sing a Black girl's song the unpublished work of Ntozake Shange - Shange, Ntozake 1948-2018 (Legacy Lit, Hachette Book Group, 2023)
"In the late 60s, Ntozake Shange was a young student at Barnard College discovering her budding talent as a writer, publishing in her school's literary journal, and finding her unique voice. By the time she left us in 2018, Shange had scorched blazing trails across countless pages and stages, redefining genre and form as we know it. Sing a Black Girl's Song is a new posthumous collection of unpublished works from throughout the life of this seminal Black feminist writer. In these pages we meet young Shange, learn the moments that inspired for colored girls who have considered suicide/when the rainbow is enuf..., travel with an eclectic family of musicians, sit on "The Couch" opposite Shange's therapist, and discover plays written after for colored girl's' international success. Sing a Black Girl's Song houses the literary rebel's politically charged verses from the Black Arts Movement era alongside her signature tender rhythm and cadence that capture the minutia and nuance of Black life, and is a long-lasting gift from one of the fiercest and most highly celebrated artists of our time"--
Keywords: American poetry / 20th century; American drama / 20th century; African American women authors / 20th century; Poésie américaine / 20e siècle; Théâtre américain / 20e siècle; Écrivaines noires américaines / 20e siècle; FICTION / Feminist; LITERARY COLLECTIONS / American / African American & Black; LITERARY COLLECTIONS / Essays; LITERARY COLLECTIONS / Women Authors; POETRY / American / African American & Black; POETRY / Women Authors; American poetry; American drama; African American women authors; 20th century; Poetry; Drama; Essays; Fiction; poetry; Poésie; Théâtre; Romans; Anthologie